Comparative proteomic analysis of four biotechnological strains Lactococcus lactis through label-free quantitative proteomics - Marques Da Silva, Wanderson (2018)
Lactococcus lactis is a bacteria with high biotechnological potential, where is frequently used in the amino acid production and production of fermented dairy products, as well as drug delivery systems and mucosal vaccine vector. The knowledge of a functional core proteome is important extremely for both fundamental understanding of cell functions and for synthetic biology applications. In this study, we characterized the L. lacits proteome from proteomic analysis of four biotechnological strains L. lactis: L. lactis subsp. lactis NCDO2118, L. lactis subsp. lactis IL1403, L. lactis subsp. cremoris NZ9000 and L. lactis subsp. cremoris MG1363. Our label-free quantitative proteomic analysis of the whole bacterial lysates from each strains resulted in the characterization of the L. lactis core proteome that was composed by 586 proteins, which might contribute to resistance of this bacterium to different stress conditions as well as involved in the probiotic characteristic of L. lactis. Kegg enrichment analysis shows that ribosome, metabolic pathways, pyruvate metabolism and microbial metabolism in diverse environments were the most enriched. According to our quantitative proteomic analysis, proteins related to translation process were the more abundant in the core proteome, which represent an important step in the synthetic biology. In addition, we identified a subset of conserved proteins that are exclusive of the L. lactis subsp. cremoris or L. lactis subsp. lactis, which some are related to metabolic pathway exclusive. Regarding specific proteome of NCDO2118, we detected ‘strain-specific proteins’. Finally, proteogenomics analysis allows the identification of proteins, which were not previously annotated in IL1403 and MG1363. The results obtained in this study allowed to increase our knowledge about the biology of L. lactis, which contributes to the implementation of strategies that make it possible to increase the biotechnological potential of this bacterium.